Analysis of the Performance Community Empowerment, Women, and Child Protection Service of Jambi City: Perspective of Islamic Family Law and Education - Lutfi (Darul Ilmi Bina Insan Foundation, 2026)
his study aims to analyze the performance of the Jambi City DMPPA in implementing Law Number 35 of 2014 concerning Child Protection, reviewed from the perspective of education and Islamic family law. This study uses a qualitative approach with descriptive analytical methods. The results show that the performance of the Jambi City DMPPA has been positive and in line with the principles of Islamic family law, which is realized through various programs such as socialization, the formation of childcare groups, and training in supporting holistic child protection. However, policy implementation still faces several obstacles, including budget constraints, weak inter-agency coordination, and low community participation, so that program implementation is not optimal and not evenly distributed. From an educational perspective, educational institutions play a strategic role in instilling Islamic-based child protection values, such as compassion, justice, and responsibility. The scientific contribution of this study presents an integrative perspective between child protection policies, education, and Islamic family law as a basis for strengthening the implementation of child protection more effectively and sustainably. Synergy is needed between the government, educational institutions, families, and communities, as well as strengthening coordination and funding to ensure the implementation of effective child protection.